Applications Selling Goods at Suka Maju Electronic Stores - Muhammad Faishal; Agung Susilo Yuda Irawan; Didi Juardi (Jurnal Ilmiah Wahana Pendidikan, 2022)
In this time technology is growing very rapidly. Technological developments can also be used in a variety of ways, one of which is in stores. Many stores still use the system of selling and buying manually, such as the Suka Maju Electronics Store. Using the manual system will take longer and the sale or purchase process becomes inefficient.Therefore the author makes a sales application at Suka Maju Electronics Store Java-based by using Neatbeans and MySQL. This application is used to process transactions and other services at Suka Maju Electronics Store. Making this application aims to improve services and facilitate users in the sales process, stock addition, and minimizing errors in making reports